Analisis Content Creator, Social Media Engagement, Customer Trust Terhadap Loyalitas Pelanggan Daviena Skincare di Jawa Tengah - Santang, Nyimas Ayu Rara; Farida, Ida; Putra, Febrianur Ibnu Fitroh Sukono; Setiawan, Aries (Faculty of Economics and Business Universitas Dian Nuswantoro, 2026)
This research is driven by the intense competition within the beauty industry and the emergence of negative issues regarding alleged